Desenvolvimento do protocolo de produção do radiofármaco colina (11C) para utilização em PET/CT : síntese e controle de qualidade - Hood, Tiago Leal Scott (2019)
Nuclear medicine is a medical specialty that uses radiotracer for generation of functional images. This type of image allows the visualization, quantification or even in vivo characterization of biochemical processes, metabolic, biomarkers and receptors, that can show pathological alterations in a non-invasive way. Among the functional imaging modalities available is Positron Emission Tomography / Computed Tomography (PET / CT), which uses radiopharmaceuticals such as Choline (11C) in the study of specific diseases. This radiotracer is mainly used to detect the recurrence of prostate cancer. Therefore, this work aimed to the development of the synthesis process of Choline (11C) radiopharmaceutical. A synthesizer GE Healthcare module TRACERLab FXC-Pro powered by carbon-11 radioisotopes was used for production. These radioisotopes were produced in a cyclotron GE Healthcare model PETtrace through the nuclear reaction 14N(p,α)11C. The synthesis of Choline (11C) was carried out by methylation of the precursor N,N-Dimethylaminoethanol (DMAE) in the C18 CM-Pak. Elution and formulation of the product were performed with 0.7 mL of ethanol and 6.3 mL of 0.9% (sterile and pyrogen-free) saline solution. Sterilization was performed by membrane filtration of 0.22 μm. The finished product was subjected to the quality control assays as radionuclidic identity and purity, radiochemical purity, residual solvents, pH, sterility, filtering membrane test and bacterial endotoxins. The process developed proved adequate for the production of the Choline (11C). The modulus was easily adapted and the methylation reaction of DMAE was reproducible with uncorrected radiochemical yield of 32.35 ± 5% (n = 2) for conversion of 11CH3I to Choline (11C). The quality control methodologies were defined and the batches produced were tested. The residual solvent content of ethanol was less than 10% and less than 20 μg/mL of DMAE for all batches produced. The analysis of radiochemical purity has proved to be one of the greatest challenges of development. The chemical similarity of Choline (11C) and saline, also present in the product, make it difficult to separate the chromatographic peaks. The mean pH found was 5 ± 0.27 (n = 16) and the radionuclide identity allowed to identify the carbon-11 radioisotope with an average half-life of 20.41 ± 0.08 min (n = 16). Biological assays confirmed the sterility and apyrogenicity of Choline (11C).